A costimulatory chimeric antigen receptor targeting TROP2 enhances the cytotoxicity of NK cells expressing a T cell receptor reactive to human papillomavirus type 16 E7 - Poorebrahim, Mansour; Quirós Fernández, Isaac; Marmé, Frederik; Burdach, Stefan EG.; Cid Arregui, Angel (Cancer letters, 2023)
Immune cells modified to express a tumor-reactive T cell receptor (TCR) have shown limited efficacy as stand-alone therapy against solid tumors. Genital and oropharyngeal carcinomas induced by human papillomavirus (HPV) type 16 express constitutively its E6 and E7 oncoproteins, which makes them convenient targets for adoptive cell immunotherapy. However, viral antigen presentation by tumor cells is low and limits the anti-tumor efficacy of CD8+ T cells. To enhance the functionality of immune effector cells, we have devised a strategy combining a costimulatory chimeric antigen receptor (CAR) with a TCR. We used a clinically tested TCR specific to E7 (E7-TCR) of HPV16 and a newly constructed CAR targeting the trophoblast cell surface antigen 2 (TROP2), which carried the intracellular costimulatory domains CD28 and 4-1BB, but was devoid of the CD3ζ domain. Flow cytometry analyses showed a notable upregulation of activation markers and of cytolytic molecule release by NK-92 cells genetically engineered to express CD3, CD8 and both E7-TCR and TROP2-CAR, after co-incubation with HPV16+ cervical cancer cells. Furthermore, the E7-TCR/TROP2-CAR NK-92 cells demonstrated enhanced antigen-specific activation and augmented cytotoxicity against tumor cells compared with NK-92 cells expressing the E7-TCR alone. A costimulatory TROP2-CAR can synergistically cooperate with the E7-TCR in NK cells thereby enhancing their signaling strength and antigen-specific cytotoxicity. This approach might improve the outcome of adoptive cell immunotherapies for HPV16+ cancer patients that are currently under investigation.
Online verfügbar: 20. Mai 2023, Artikelversion 1. Juni 2023
Gesehen am 14.02.2024